Simultaneous low- and high-mass star formation in a massive protocluster: ALMA observations of G11.92-0.61 - Cyganowski, Claudia J.; Kruijssen, Diederik (Monthly notices of the Royal Astronomical Society, 2017)
We present 1.05 mm Atacama Large Millimeter/submillimeter Array (ALMA) observations of the deeply embedded high-mass protocluster G11.92−0.61, designed to search for low-mass cores within the accretion reservoir of the massive protostars. Our ALMA mosaic, which covers an extent of ∼0.7 pc at sub-arcsecond (∼1400 au) resolution, reveals a rich population of 16 new millimetre continuum sources surrounding the three previously known millimetre cores. Most of the new sources are located in the outer reaches of the accretion reservoir: the median projected separation from the central, massive (proto)star MM1 is ∼0.17 pc. The derived physical properties of the new millimetre continuum sources are consistent with those of low-mass prestellar and protostellar cores in nearby star-forming regions: the median mass, radius and density of the new sources are 1.3 M⊙, 1600 au and n$$_{\rm H_2}\sim 10^{7}$$ cm−3. At least three of the low-mass cores in G11.92−0.61 drive molecular outflows, traced by high-velocity 12CO(3-2) (observed with the Submillimeter Array) and/or by H2CO and CH3OH emission (observed with ALMA). This finding, combined with the known outflow/accretion activity of MM1, indicates that high- and low-mass stars are forming (accreting) simultaneously within this protocluster. Our ALMA results are consistent with the predictions of competitive-accretion-type models in which high-mass stars form along with their surrounding clusters.